Design of magnetic kappa-carrageenan-collagen bioinks for 3D bioprinting - Almeida, Duarte (2024)
Funding Information: This project also received financial support from \u201Cla Caixa\u201D Foundation (ID 100010434) LCF/BQ/PI22/11910025. Publisher Copyright: © The Author(s) 2024.